Gestión operativa de las haciendas bananos hoyos cobo y su incidencia en la rentabilidad, periodo contable año 2012 - Gaona Bustamante, Mayra Alejandra (2015)
Thepresent research is focused on determining the impact of business management on profitability of Haciendas Bananos Hoyos Cobo as general objective. According to this, it was important to review the financial data of the periods 2011 – 2012 in which case the farms are located in Valencia Canton. The universe is formed byfarms because of the information thatwas required such as: the executed operations as well as the accounting information of the periods under study by the financial part. The collection of information was obtained by applying the questionnaire and holding a meeting with the administrative staff that are integrated by the Owner, Financial Manager and Operations Manager. In addition, surveys were applied to the operational staff that includes Personnel Manager in order to determine how the work is executed and obtain data as a result of his management....